Konseptualisasi Metafora Bentuk Fisik Ideal dan Tidak Ideal dalam Bahasa Sumbawa: Conceptualization of Ideal and non-Ideal Physical Form Metaphors in the Sumbawa Language - Elya Febriani; Hani Agustina; Rinda Widya Ikomah (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study examines conceptual metaphors in the Sumbawa language that reflect the ideal and non-ideal physical forms of its people. Using a qualitative-descriptive approach, data were collected from 12 informants by interviews and corroborated with other sources including dictionaries, other online sources, and confirmation from native speakers. This method was used because it allows the identification and classification of metaphors used to reflect or conceptualize the views of the Sumbawa people. The analysis results show that shape metaphors in the Sumbawa language function not only as rhetorical tools, but also as cognitive and cultural mechanisms in shaping physical form standards in Sumbawa society. Data identification shows the most dominant source domains such as food, flora, cosmos, animals, nature, objects, humans, and even mystical things. Meanwhile, the most dominant target domains projecting metaphors of ideal and non-ideal physical forms include parts of the face, body parts, and the body as a whole. These source and target domains were then mapped to conceptualize ideal and non-ideal physical forms in the Sumbawa language. For example, in the expressions “batata bulan satangal” (crescent forehead) and “mara bulan buntar subuh” (like a full moon at dawn). In the data, the moon is understood as a symbol of beauty, light, and perfection, thus mapping it to the human body, which is considered ideal. Conversely, mystical domains, such as the expressions "yam serusu" (like a sleep-disturbing genie) and "yam bura Labu" (like a Labu's magic), are used to describe bodies considered sub-ideal, disproportionate, and unsightly. Thus, this study demonstrates that conceptualization of the body in Sumbawa society is influenced not only by physical experience but also by local cultural belief systems. This research is expected to contribute to the development of cognitive linguistics studies by presenting empirical data from regional languages ​​that have previously been underexplored.